Investigation of aphids on Rosaceae in Ghamsar region, Kashan - Maranjian, Zeinab; Shayestehfar, Alireza; Mahdi Talebi, Seyed; Nourollah Mousavi, Seyed (Journal of Biological Studies, 2022)
Many studies have shown that aphids are one of the most important pests of plants. At the same time, not much information is available about aphids on plants in the Ghamsar region of Kashan. Based on this, the present study examines the existing aphids on the Rosaceae in the Ghamsar region of Kashan ni 2019. During this basic research, aphid samples from leaves and branches infected with aphids of Rosaceae plants in the Kashan Ghamsar region were collected monthly in 2019 and transferred to the Arak University laboratory for microscopic slides. At the same time, samples were taken from the host plants. The aphid samples were collected and their host plants were identified to the species level using the available identification keys. In this study, 6 species of aphids from 5 genera belonging to the Aphididae were identified from 8 species of the Rosaceae. Among the identified species, Wahlgreniella nervata had the highest host diversity and distribution.